2022
DOI: 10.3389/fbioe.2022.865370
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Signaling Pathways in Osteoarthritis

Abstract: Osteoarthritis (OA) is a debilitating joint disease that affects millions of individuals. The pathogenesis of OA has not been fully elucidated. Obesity is a well-recognized risk factor for OA. Multiple studies have demonstrated adipokines play a key role in obesity-induced OA. Increasing evidence show that various adipokines may significantly affect the development or clinical course of OA by regulating the pro/anti-inflammatory and anabolic/catabolic balance, matrix remodeling, chondrocyte apoptosis and autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 161 publications
1
11
0
Order By: Relevance
“…An in vitro cell culture study showed that leptin could activate the NF‐κB signaling pathway to induce chondrocytes to express MMP1 and MMP13 33 . NF‐κB was also shown to be a critical factor in the adiponectin‐induced expression of bone morphogenetic protein (BMP)‐2 in osteoblasts and IL‐6 in human synovial fibroblasts 17 . Our study, in vivo and in vitro results, confirmed that NF‐κB plays an important role in FABP4‐mediated OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro cell culture study showed that leptin could activate the NF‐κB signaling pathway to induce chondrocytes to express MMP1 and MMP13 33 . NF‐κB was also shown to be a critical factor in the adiponectin‐induced expression of bone morphogenetic protein (BMP)‐2 in osteoblasts and IL‐6 in human synovial fibroblasts 17 . Our study, in vivo and in vitro results, confirmed that NF‐κB plays an important role in FABP4‐mediated OA.…”
Section: Discussionmentioning
confidence: 99%
“…16 The NF-κB signaling pathway is also a center of crosstalk in adipokine-mediated OA. 17 The NF-κB pathway has been shown to play both anti-and pro-oxidant roles in the context of oxidative stress. 18 Therefore, the purpose of this study was to explore the mechanism of FABP4 in cartilage degeneration and inflammation.…”
Section: Significance Statementmentioning
confidence: 99%
“…The hypoxia-inducible factors-2α expression causes OA by promoting Fas-mediated chondrocyte apoptosis [ 261 ]. Induced by chronic excess of glucolipid metabolism, synovium secretes adipokines, such as free fatty acids, leptin, and adiponectin, which increase the expression of cartilage-degeneration-related genes in chondrocytes [ 262 , 263 ]. Reseland et al [ 264 ] reported that leptin is released upon local mechanostimulation, which might be associated with osteoblastic development in subchondral bone remodeling.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Osteoarthritis (OA) is mainly characterized by articular cartilage degeneration, chronic mild synovitis, and subchondral bone degeneration (Wei & Bai, 2016). At the cellular microenvironment level, various factors could cause chondrocytes to become damaged and dysfunctional, including metabolic abnormalities (Zheng et al, 2021), extracellular matrix (ECM) degradation, oxidative stress, adipokines (Wang & He, 2018; Zhang, Lin, et al, 2022), and mechanical stimulation (Wang & He, 2018). These kinds of inflammation‐associated pathological changes could be seen as associated with different inflammatory factor secreting, including interleukin (IL)‐1, cyclooxygenases (COX), prostaglandin E (PGE; Cook et al, 2018; Dinarello, 2011), matrix metalloproteinase (MMP) family, components of the NF‐κB, tumor necrosis factor (TNF) family, and so forth (Stone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%